Critical Mathematical Thinking Ability Viewed from The Mathematical Disposition of Junior High School Students - Andika Dwi Pratama; Risnanosanti Risnanosanti; Nyayu Masyita Ariani (MASI Mandiri Edukasi, 2026)
This study was conducted to examine the problem that students’ mathematical critical thinking skills remain varied and are assumed to be influenced by their mathematical disposition. Therefore, this research aims to describe students’ mathematical critical thinking skills from the perspective of their mathematical disposition. This research employed a qualitative approach with a descriptive design. The subjects were six eighth-grade students from SMP IT Al-Marjan Bengkulu, categorized into high, medium, and low levels of mathematical disposition. Data were collected through a mathematical disposition questionnaire, a mathematical critical thinking skills test, and semi-structured interviews. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that students with high mathematical disposition demonstrate strong performance across all critical thinking indicators, including interpretation, analysis, evaluation, inference, and explanation. Students with medium disposition show adequate ability but lack consistency in drawing conclusions and providing logical justification. Meanwhile, students with low mathematical disposition tend to rely on procedural strategies rather than developing deeper conceptual understanding. These results confirm that mathematical disposition contributes to the quality of students’ critical thinking in mathematics.